Efficacy of Gene Therapy to Restore Cognition in Alzheimer’s Disease: A Systematic Review - Tedeschi, Desyrre V.; da Cunha, Anderson F; Cominetti, Márcia R.; Pedroso, Renata V. (Current Gene Therapy, 2021)
Background: Alzheimer's disease (AD) is the main cause of dementia and it is a progressive neurogenerative disease characterized by the accumulation of neurofibrillary tangles and senile plaques. There is currently no cure; however, some treatments are available to slow down the progression of the disease, including gene therapy, which has been investigated to have great potential for the treatment of AD. Objective: The aim of this review was to identify the efficacy of gene therapy to restore cognition in AD. Methods: A systematic review was carried out using papers published up to May 2020 and available in the Web of Science, Scopus, and Medline/PUBMED databases. Articles were considered for inclusion if they were original researches that investigated the effects of gene therapy on cognition in AD. The methodological quality of the selected studies was evaluated using the Risk of Bias Tool for Animal Intervention Studies (SYRCLE’s Rob tool) and the Jadad Scale. Results: Most preclinical studies obtained positive results in improving memory and learning in mice that underwent treatment with gene therapy. On the other hand, clinical studies have obtained inconclusive results related to the delivery methods of the viral vector used in gene therapy. Conclusion: Gene therapy has shown a great potential for the treatment of AD in preclinical trials, but results should be interpreted with caution since preclinical studies presented limitations to predict the efficacy of the treatment outcome in humans.
Keywords: therapy